1997
DOI: 10.1073/pnas.94.12.6244
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific de- N -glycosylation of diglycosylated ovalbumin in hen oviduct by endogenous peptide: N -glycanase as a quality control system for newly synthesized proteins

Abstract: Hen ovalbumin (OVA) is known to exist as a singly N-glycosylated form with a glycan chain on Asn-292 in egg white. Previous studies showed that di-N-glycosylated form of OVA [Di-OVA; CHO-Asn-292͞CHO-Asn-311 (CHO, N-glycan chain)], which has two N-glycan chains on Asn-292 and Asn-311, was expressed only transiently in hen oviduct. Di-OVA was not found in egg white, suggesting that this form cannot be secreted normally and may possibly be converted to mono-N-glycosylated OVA (CHO-Asn-292͞Asp-311) by the action o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 51 publications
(48 reference statements)
1
71
0
Order By: Relevance
“…Localization of these proteins around the ER periphery indicates that they could be involved in the ERAD process (23). PNGase has been reported to be present in the ER (24), microsomes (25), and the cytosol (26). Some studies using immunofluorescence suggest the association of proteasomes with the cytosolic face of ER membrane both in mammalian cells (27,28) and in yeast (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…Localization of these proteins around the ER periphery indicates that they could be involved in the ERAD process (23). PNGase has been reported to be present in the ER (24), microsomes (25), and the cytosol (26). Some studies using immunofluorescence suggest the association of proteasomes with the cytosolic face of ER membrane both in mammalian cells (27,28) and in yeast (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…The degree of N-glycosylation of component H appeared to be higher than that of component L or hen egg OVA. Alternatively, Suzuki et al 20) have reported that in the oviduct only di-N-glycosylated OVA was cleaved immediately at Asn-311 by PNGase F, and that it is was secreted as the mono-N-glycosylated form at Asn-292. To investigate further the binding site of a carbohydrate chain on components H and L, we attempted to treat the recombinant proteins together with hen egg OVA with PNGase F in the non-denaturing condition without 2-mercaptoethanol and SDS.…”
Section: Deglycosylation and Glycosylation Profilingmentioning
confidence: 99%
“…As discussed previously, PNGase has been reported to be localized in the cytosol (Suzuki et al, 1998) and also reported to be associated with the ER membrane (Suzuki et al, 1997;Katiyar et al, 2004). Conflicting evidence also suggested localization in the ER lumen (Weng and Spiro, 1997).…”
Section: Discussionmentioning
confidence: 72%
“…In fact, in the studies of Wiertz et al (1996) only the deglycosylated forms of MHC class I molecules were noted to be associated with the Sec61 complex of the ER membrane, indicating that glycoproteins in this channel must also encounter N-glycanase. Another example of the ER membranelocalized deglycosylation is the protein ovalbumin in which site specific N-deglycosylation was attributed to an ER-situated N-glycanase (Suzuki et al, 1997). In contrast to HCs, TCR␣ apparently utilizes a different dislocation machinery for degradation (Misaghi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation